Effectiveness of Moderate Intensity Interval Training as an Index of Autonomic Nervous Activity. (10th November 2016) - Kai, Satoru; Nagino, Koji; Ito, Takayoshi; Oi, Rie; Nishimura, Kazushi; Morita, Shuhei; Yaoi, Riyo
Abstract : The purpose of this study was to examine the effects of moderate intensity interval training from the change of the autonomic nervous activity. Ten male volunteers aged 21-22 years were studied. After 10-minute rest in a seated position, the subjects were asked to perform the strength of moderate cycling exercise in ergometer. Cycling rate was done in 50 times/min. Load resistance of the ergometer was set to 2.0 kgm. Subjects paused the exercise when the heart rate becomes 120 beats/min. Subjects have resumed the exercise when the heart rate returns to the value at rest. This trial was repeated twice. The experiment was ended when the heart rate of the subjects has returned to resting level. When the heart rate during exercise is maintained to less than 120 beats/min, sympathetic nerve activity during exercise did not work actively compared to the baseline. Vagus nerve activity after exercise cessation exceeds the baseline. It is clarified that the exercise as well as activating the vagus nerve activity stimulates the total autonomic nervous activity. It has revealed that at the time of interval training at moderate load the vagus nerve activity can be carried out.